2017
DOI: 10.3390/ijms18081698
|View full text |Cite
|
Sign up to set email alerts
|

Scar Prevention and Enhanced Wound Healing Induced by Polydeoxyribonucleotide in a Rat Incisional Wound-Healing Model

Abstract: High-mobility group box protein-1 (HMGB-1) plays a central role in the inflammatory network, and uncontrolled chronic inflammation can lead to excessive scarring. The aim of this study was to evaluate the anti-inflammatory effects of polydeoxyribonucleotide (PDRN) on scar formation. Sprague-Dawley rats (n = 30) underwent dorsal excision of the skin, followed by skin repair. PDRN (8 mg/kg) was administered via intraperitoneal injection for three (PDRN-3 group, n = 8) or seven (PDRN-7 group, n = 8) days, and HMG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 33 publications
2
44
0
Order By: Relevance
“…Effect of PDRN size on wound closure in mice skin. Multiple previous studies have demonstrated that PDRNs promote wound healing in various animal models (6,10,(18)(19)(20). To evaluate the effect of PDRNs on wound healing, 8-week old hairless (SKH1) mice were given different sizes of PDRNs daily for a week.…”
Section: Resultsmentioning
confidence: 99%
“…Effect of PDRN size on wound closure in mice skin. Multiple previous studies have demonstrated that PDRNs promote wound healing in various animal models (6,10,(18)(19)(20). To evaluate the effect of PDRNs on wound healing, 8-week old hairless (SKH1) mice were given different sizes of PDRNs daily for a week.…”
Section: Resultsmentioning
confidence: 99%
“…PRP contains high amounts of platelets, and owing to the fact that platelets release some of the growth factors involved in modulating the regeneration process, it is not surprising that the MSC-devoid FMs still have a regenerative effect on the VML site. The inflammation phase in the FM-R transplantation groups (with/without MSCs) passed faster than the Sham group [55]. Growth factors released from FM-Rs may also have an influence in decreasing scar tissue formation.…”
Section: Hande Histochemical Findings: Fibrosis or Regenerationmentioning
confidence: 96%
“…Some of these same mediators have also been studied in adult wound healing models. For example, HMGB-1 has been linked to scar formation [ 88 ] and blocking PGE 2 production with drugs that inhibit cyclooxygenase-2 activity has been shown to reduce scar formation in adult incisional wound models [ 89 , 90 ] . Other pro-inflammatory cytokines that have been linked to cutaneous scar formation and/or collagen production in adult scar/fibrosis models include IL-17 [ 91 ] and monocyte chemoattractant protein-1 [ 92 , 93 ] .…”
Section: Functional Data Linking Inflammation and Scarringmentioning
confidence: 99%